The cost of dialysis renal replacement therapy for end-stage renal disease patients in Ukraine - M. Kolesnyk; L. Liksunova; T. Selezneva; T. Maistrenko (Ukrainian Journal of Nephrology and Dialysis, 2019)
Expenses for the treatment of end-stage renal disease (ESRD) patients with dialysis renal replacement therapy (DRRT) during the 2018 year constituted 2 billion 922 million 460 thousand UAH. Reimbursement from the state budget constituted 1 billion 44 million 800 thousand UAH. Expendable materials were the main component of DRRT. The share of the expendable materials price from total cost for hemodialysis and hemodiafiltration constituted 66%, for continuous ambulatory peritoneal dialysis and automatic peritoneal dialysis was 86.3% and 92.2%, respectively.The results of the investigation can be used for the development of a diversification model (state budget – local budgets – other sources) of financial expenses for the provision of dialysis treatment in ESRD patients as a part of the state program (strategy) health care finance and service delivery.